Technology Adoption Among University Scholars: Institutional Repositories Case Study - Rifai, Agus (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The emergence of institutional repositories (IRs) is seen as a new scholarly publishing model. This study aims to understand the adoption of technology from the perspective of information behavior by exploring users’ characteristics of information need, awareness, and need of IRs concerning the use of IRs. Three hundred university lecturers from six state Islamic universities were observed to obtain their perception of the need for IRs using a questionnaire survey. Partial least square structural equation modeling was used for data analysis. The analyses of measurement and structural models were conducted to validate the relationship between the observed variables. The study found that the information-seeking behavior model has partially explained the use of repositories among university scholars by 53,5%. The results mean that other factors influence the use of IRs that are not examined by this research.